Hepatitis C-related knowledge, attitudes and perceived risk behaviours among people who inject drugs in Kenya: A qualitative study. Issue 6 (3rd June 2022) - Akiyama, Matthew J.; Muller, Abbe; Huang, Owen; Lizcano, John; Nyakowa, Mercy; Riback, Lindsey; Ross, Jonathan; Bundi, Henry; Kulabi, Euphrasia Shitachi; Mwangi, Ann Muthoni; Musyoki, Helgar; Cherutich, Peter; et al.
ABSTRACT: Despite disproportionately high rates of Hepatitis C (HCV) among people who inject drugs (PWID) in low- and middle-income countries (LMICs), understanding of HCV-related knowledge, attitudes and perceived risk behaviours among this population remains limited. We aimed to elucidate knowledge, attitudes and experiences that could minimise transmission risk and maximise HCV treatment engagement among PWID in Kenya following the integration of HCV screening and education with needle and syringe programmes in drop-in-centres (DICs). We recruited 40 PWID with chronic HCV attending DICs in Nairobi and Coastal Kenya. Semi-structured interviews revealed a general understanding of HCV and awareness of HCV risk behaviours among participants; however, many felt limited control over their transmission risk due to factors such as 'local doctors', or individuals who perform a high volume of high-risk injections. Financial barriers, distance to clinic, poor health status and HCV-related stigma were all noted as barriers to HCV treatment. In conclusion, basic knowledge of and motivation for HCV treatment among PWID accessing DICs in Kenya was high; however, structural barriers and stigma complicate access to care. Local education programmes can address knowledge gaps, and behavioural and structural interventions can maximise the impact of HCV care in LMICs.